2014
DOI: 10.3928/01477447-20140430-54
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of 3 Posterior Fixation Techniques in the Lumbar Spine

Abstract: This study compared the biomechanics of 3 fixation techniques: bilateral pedicle screw (BPS) fixation, unilateral pedicle screw (UPS) fixation, and UPS supplemented with translaminar facet screw (UPS+TLFS) fixation. The study was conducted in an L3-L5 finite element model. Three different finite element models were created by adopting different fixation techniques after removal of the left L3-L4 and L4-L5 facet joints. A 500-N compressive preload combined with 8-NM moment were applied in 3 finite element model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
0
19
1
Order By: Relevance
“…The addition of the TLFS to the UPS confers to it intermediate stability, superior to the UPS and inferior to the BPS in stability. However, this is different from what Gong et al 11 demonstrated in a finite element model, in which they revealed that UPSFS fixation was superior to either UPS or BPS fixation in improving stability and reducing stress biomechanically. The reason for this discrepancy might be explained by the variances of these two study methods.…”
Section: Discussioncontrasting
confidence: 51%
“…The addition of the TLFS to the UPS confers to it intermediate stability, superior to the UPS and inferior to the BPS in stability. However, this is different from what Gong et al 11 demonstrated in a finite element model, in which they revealed that UPSFS fixation was superior to either UPS or BPS fixation in improving stability and reducing stress biomechanically. The reason for this discrepancy might be explained by the variances of these two study methods.…”
Section: Discussioncontrasting
confidence: 51%
“…Accordingly, several modified techniques have been assessed by finite element analysis and biomechanical tests, for example, unilateral pedicle screw (UPS), UPS with contralateral translaminar facet joint screw (UPS þ TFS) and etc. The results show that the stability of UPS þ TFS is similar to that of BPS for both 1-level and 2-level lumbar spinal disorders [5][6][7]. Moreover, some recent clinical studies also indicate TLIF using UPS þ TFS by paramedian mini-incision is a safe, feasible and effective method to treat one or two segment lumbar degenerative disorders [8,9].…”
Section: Introductionmentioning
confidence: 72%
“…A previous infinite element analysis showed that UPS + TLFS fixation is superior to either UPS or BPS in improving stability and reducing stress (Gong et al, 2014). However, all the mechanical parameters were set under normal conditions for infinite element model.…”
Section: Discussionmentioning
confidence: 99%
“…The finite element model could accurately simulate the movement of the lumbar spine in all directions to investigate the changes in internal stress accumulated on multiple areas of the lumbar spine and fixation devices during movement. In a previous study, an infinite element analysis showed that UPS + TLFS fixation is superior to either UPS or BPS in improving stability and reducing stress (Gong et al, 2014). However, all the mechanical parameters were set under normal conditions for the finite element model and some conditions seen in clinical settings were ignored when experimental parameters were set, such as vertebral body flexibility and effect of muscle tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation